Production, characterization and application of activated carbon from brewer’s spent grain lignin - Mussatto, Solange I. (2010)
Different types of activated carbon were prepared by chemical activation of brewer’s spent grain (BSG) lignin using H3PO4 at various acid/lignin ratios (1, 2, or 3 g/g) and carbonization temperatures (300, 450, or 600 °C), according to a 22 full-factorial design. The resulting materials were characterized with regard to their surface area, pore volume, and pore size distribution, and used for detoxification of BSG hemicellulosic hydrolysate (a mixture of sugars, phenolic compounds, metallic ions, among other compounds). BSG carbons presented BET surface areas between 33 and 692 m2/g, and micro- and mesopores with volumes between 0.058 and 0.453 cm3/g. The carbons showed high capacity for adsorption of metallic ions, mainly nickel, iron, chromium, and silicon. The concentration of phenolic compounds and color were also reduced by these sorbents. These results suggest that activated carbons with characteristics similar to those commercially found and high adsorption capacity can be produced from BSG lignin.